Research on Newly Urbanized Towns and Districts in China - 刘新静 于炜 王晓静 盛蓉 张书成 刘士林 (Shanghai jiao tong da xue xue bao, 2014)
Since the last decade the central government endeavors to promote large scale of urbanization in China. Lots of new urban towns and districts are taking shape. Outline of the 12th Five-year Plan released by the central government points out that the new towns and districts are to be regulated. But few researches are considering the new towns and districts especially in the spatial distributive pattern and status in China. Given this situation this paper, after sorting out the world-wide research and development of new urban towns and districts, gives definitions of broad and narrow meanings. Based on the broad meaning definition, the database of new towns and districts in China is established. This paper then conducts a preliminary analysis of the new towns and districts. Then the two-step work plan and the advices are also proposed to further improve the research and practice of its kind in China.